Inovasi Camilan Sehat Ikan Bandeng Tingkatkan Gizi Remaja Putri Pangkajene - Awaluddin, Sri Prilmayanti; Rustam, Rustam; Khair, Andi ummul; Azis, Indrawan; Nurani, Nurani; Muntasir, Muntasir (Jurnal Abdimas Multidisiplin, 2025)
Purpose: This service aims to increase the knowledge and skills of young women in processing milkfish into healthy snacks that are appealing, thus promoting better nutritional intake and economic opportunities in Bonto Langkasa, Minasa Te’ne District, Pangkajene and Islands Regency. Methodology/approach: This activity was carried out in Bonto Langkasa with participating adolescent girls as the main target. The project adopted a participatory approach, including nutritional counseling, hands-on training using simple, locally sourced tools, and digital marketing workshops. Materials used were fresh milkfish, healthy additives, and packaging sourced from local markets. Pre- and post-tests, as well as follow-up surveys, were conducted to measure changes in knowledge, skills, and snack production rates. Results/findings: The program successfully increased participants’ knowledge about nutrition and practical skills in producing healthy milkfish-based snacks. Several participants started small-scale production, selling snacks in their communities. The project also improved participants' digital marketing competencies. Conclusion: Community service that focuses on innovative, healthy snacks using local resources, such as milkfish, can bridge nutritional knowledge-practice gaps, contribute to adolescent health, and foster economic opportunities for young women. This model is sustainable and replicable in other fishing communities. Limitations: Milkfish snack innovation is limited by simple technology, cultural preferences, basic nutritional focus, limited digital marketing, and narrow youth coverage, requiring further studies in other regions. Contribution: The contribution of this community service is to enhance nutritional knowledge, and develop healthy snack production skills, empower young women economically, optimize local milkfish production, and expand marketing through digital means.